2018
DOI: 10.1080/00324728.2018.1457794
|View full text |Cite
|
Sign up to set email alerts
|

A survival analysis of the last great European plagues: The case of Nonantola (Northern Italy) in 1630

Abstract: This paper develops the first survival analysis of a large-scale mortality crisis caused by plague. For the time-to-event analyses we used the Cox proportional hazards regression model. Our case study is the town of Nonantola during the 1630 plague, which was probably the worst to affect Italy since the Black Death. Individual risk of death did not depend on sex, grew with age (peaking at ages 40-60 and then declining), was not affected by socio-economic status, and was positively associated with household siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…The available evidence suggests that the Black Death was "massive and indiscriminate, making no exception to factors such as personal hygiene, health, age, sex, or social class" (Christakos et al, 2005, 150). This is supported by recent studies of plague outbreaks (Alfani and Bonetti, 2018…”
Section: The Epidemiological Shocksupporting
confidence: 74%
“…The available evidence suggests that the Black Death was "massive and indiscriminate, making no exception to factors such as personal hygiene, health, age, sex, or social class" (Christakos et al, 2005, 150). This is supported by recent studies of plague outbreaks (Alfani and Bonetti, 2018…”
Section: The Epidemiological Shocksupporting
confidence: 74%
“…In a study of mortality rates from archival evidence rather than use of model populations, Isabelle Séguy et al (2006) found that plague mortality rates increased with age. The only other work of which we are aware that includes a reconstruction of the complete age structure of the population, applying survival analysis to the 1629-1631 plague in northern Italy, concluded that the young (<10 years of age) were less affected and that the risk of dying peaked much later than had been previously assumed, between ages 40 and 60 (Alfani and Bonetti 2016).…”
Section: Mortality By Sex Age and Socioeconomic Statusmentioning
confidence: 99%
“…Guido Alfani and Samuel K. used this method for a transmission. Alfani and Marco Bonetti (2016) again working on 1630 Nonantola, survival analysis techniques and supported human-to-human transmission.…”
Section: Figure 1 American Demographic Collapse Following the Columbimentioning
confidence: 99%
“…The 1400 epidemic reflects a major post-Black Death plague recurrence that was generalized in Europe [6]. In Dijon, the death rate of the 2,149 registered heads of household was 15.1%, which was comparable to that of one of the last great European plagues [22]. The second epidemic developed over two years [6,29,30], in 1438 (with a death rate of 5.5% among the 1,951 registered heads of household) and in 1439 (with a death rate of 10.4% among the 1,814 registered heads of household), resulting in a cumulated death toll comparable to that of 1400.…”
Section: Years Of Epidemicmentioning
confidence: 99%
“…Taking into account host susceptibility has brought back a long-standing debate about death selectivity during historical plagues [4,13,14]. The influences of frailty, age, gender, and socioeconomic status on plague-related mortality were recently reevaluated by paleodemographic methods [15][16][17][18] and by the direct and extensive analysis of historical sources [19,20] combined with the calculation of fatality rates [21] or of individual's risk of death [22]. This has contributed to a better knowledge of the disease despite a number of conflicting results.…”
Section: Introductionmentioning
confidence: 99%